2021
DOI: 10.3389/fonc.2021.671144
|View full text |Cite
|
Sign up to set email alerts
|

miR-1258 Attenuates Tumorigenesis Through Targeting E2F1 to Inhibit PCNA and MMP2 Transcription in Glioblastoma

Abstract: MicroRNAs are a group of endogenous small non-coding RNAs commonly dysregulated in tumorigenesis, including glioblastoma (GBM), the most malignant brain tumor with rapid proliferation, diffuse invasion, and therapeutic resistance. Accumulating evidence has manifested that miR-1258 exerts an inhibitory role in many human cancers. However, the expression pattern of miR-1258 and its potential function in GBM tumorigenesis remain unclear. In this study, we reported that miR-1258 expression decreased with the ascen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…These findings reveal that targeting ferroptosis may help to develop novel therapeutic approaches to treat glioblastoma. microRNAs (miRNAs) are kinds of endogenous gene regulators through binding to the 3 ′ -untranslated region (UTR) of targeted messenger RNAs, and play critical roles in a broad range of biological processes, including ferroptosis and glioblastoma [16][17][18][19]. Wang et al previously revealed that miR-210-3p level was elevated in human glioblastoma tissues and positively correlated with the clinic stage.…”
Section: Introductionmentioning
confidence: 99%
“…These findings reveal that targeting ferroptosis may help to develop novel therapeutic approaches to treat glioblastoma. microRNAs (miRNAs) are kinds of endogenous gene regulators through binding to the 3 ′ -untranslated region (UTR) of targeted messenger RNAs, and play critical roles in a broad range of biological processes, including ferroptosis and glioblastoma [16][17][18][19]. Wang et al previously revealed that miR-210-3p level was elevated in human glioblastoma tissues and positively correlated with the clinic stage.…”
Section: Introductionmentioning
confidence: 99%
“…The average survival time of patients with glioma is 12–15 months, the 5‐year survival rate is <5%, and the survival and prognosis of patients with GBM are worse 22 ; thus, it is important to evaluate the patient's prognosis. High expression of miR‐1258 , miR‐935 and miR‐128‐3p was associated with better overall survival (OS) in patients with GBM, 23 , 24 , 25 while low miR‐542‐3p and miR‐221/222 clusters expression was associated with better OS in patients with GBM. 26 , 27 Previous studies evaluated the effect of cell‐free circulating RNA on patients with GBM.…”
Section: Microrna Smentioning
confidence: 99%
“…MiR‐1258 can inhibit GBM cell proliferation, invasion and migration and control cell cycle by targeting transcription factor E2F1. 25 Xu et al 24 indicated that miR‐128‐3p could act on the transcription factor RUNX to enhance the sensitivity of patients with GBM to chemotherapeutic drugs and inhibit the proliferation of tumour cells. In addition, forkhead box M1 ( FOXM1 ), a member of the Forkhead Box transcription factor family, controls cell cycle processes mediated by miR‐370‐3p , which enhanced the sensitivity of patients with GBM to temozolomide.…”
Section: Microrna Smentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al [57] reported that pcna expression in gastric cancer tissues was significantly upregulated compared with normal tissues, and the positive expression of pcna is a risk factor for the prognosis of patients with gastric cancer. Qin et al [58] reported that in glioblastoma (GBM), a type of microRNA (miR-1258), inhibits pcna transcription by directly targeting e2f1, which provides a new potential target for GBM therapy and other e2f1-driven cancers. According to the above reports, the up-regulated expression of pcna is related to the poor prognosis of patients with tumors, which is similar to the results we analyzed using Kaplan-Meier graphs, indicating that the increased expression of pcna is related to poor 5-and 10-year OS and RFS in sarcoma A growing body of evidence indicates that the tumor microenvironment plays an important role in the regulation of the proliferation and metastasis [59,60].…”
Section: Expression Of P16 P53 and Pcna Genes And Degree Of Immune In...mentioning
confidence: 99%